Pembentukan POKDARWIS untuk Pengembangan Potensi Agrowisata di Desa Beji, Kapanewon Ngawen, Kabupaten Gunung Kidul - Dharomesz, Vonezyo Yupanzara (Jurnal Atma Inovasia, 2023)
Kuliah Kerja Nyata (KKN) is one of the mandatory courses that must be fulfilled by Universitas Atma Jaya Yogyakarta students in order to obtain a bachelor's degree. The implementation of the Community Service Program for the 2021/2022 academic year is carried out online considering the spread of the COVID-19 called KKN Society 5.0. Group 26 as part of the UAJY KKN consisted of 10 students from various study programs at UAJY accompanied by one lecturer who got placement in Beji Village. Beji Village is located in Ngawen District, Gunungkidul Regency, Special Region of Yogyakarta. Beji village has a lot of potential in terms of culinary, culture, and nature tourism. Beji Village relies on the agricultural sector as a driving force for the village economy. Group 26 has 2 work programs to support Beji Village so that it can become an agro-tourism village so that other potentials from Beji Village can also be further developed. The program consists of the establishment of a Beji Tourism Awareness Community and the Formulation of an Agro-tourism Village Promotion Strategy. The work program is outlined in the form of group reports, pocketbook e-books, village potential e-books, and explanatory videos. It is hoped that the 2 programs that have been planned can become a source of reference for the village government in formulating village policies and become a guide for villagers in developing the potential of Beji Village.